THE ROLE OF DISEASE ACTIVITY IN THE DETERMINATION OF FUNCTIONAL STATUS AND QUALITY OF LIFE IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Taciser Kaya,; Altınay Göksel Karatepe,; Rezzan Günaydın,; Salih Ürper, (Archives of Rheumatology, 2006)
Objective: Disease activity in patients with AS is evaluated with Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). BASDAI≥4 is accepted as active disease. The effect of disease activity on functional status and quality of life was investigated in this study. Patients and Methods: 37 patients who fulfilled the modified New York criteria for AS were included in this study. The patients were divided into two groups; group 1 (BASDAI<4) and group 2 (BASDAI≥4). Functional status [Bath Ankylosing Spondylitis Functional Index (BASFI)], physical stiffness [Health Assessment Question naire-Spondyloarthropathy (HAQ-S)] and quality of life [Ankylosing Spondylitis Quality of Life (ASQoL)] were evaluated in order to compare the groups. Results: There were 17 patients in group 1 (M/F= 16/1) and 20 patients in group 2 (M/F= 14/6). The mean of ages and disease duration were 38.1±12.4 year and 102.7±88.0 months in group 1 and 39.3±9.7 year and 98.6±74.6 months in group 2 (p=0.762, 0.879 respectively). Patients with a BASDAI ≥4 had a worse functional status evaluated with HAQ-S and BASFI than those who have a BASDAI of <4 (p=0.000). However there was no difference in respect to the level of quality of life between the groups (p=0.461). Conclusion: These results show that the cut off level of BASDAI≥4 choosen for determination of disease activity is discriminatory for functional status but not for quality of life. (Rheumatism 2006; 21: 9-12)